2018
DOI: 10.3130/aijs.83.763
|View full text |Cite
|
Sign up to set email alerts
|

A Fundamental Study for the Self-Healing Performance of Heavyweight Concrete

Abstract: Water permeability tests and SEM analysis were conducted for self-healing of cracking in heavyweight concrete used as containments for radioactive substances to preventing leaching of radioactive contaminants. Within the range of this study, water permeability is reduced by self-healing at an early stage, but the internal crack width scarcely changed, with crack closure being limited to the surfaces. Also, the addition of an expansive additive led to early self-healing, presumably due to its chemical prestress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Prefabricated box culverts, a novel structural component, are gaining widespread attention within the engineering domain due to their rapid construction, minimal environmental impact, and significant economic benefits [1][2][3][4]. However, the unpredictability of high-temperature scenarios in real-world applications, such as fires and high-temperature industrial processes, places emphasis on the safety and temperature distribution of these culverts [5][6][7]. Specifically, the joints, a crucial part of the culverts, play a pivotal role in determining the overall safety of the structure under high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Prefabricated box culverts, a novel structural component, are gaining widespread attention within the engineering domain due to their rapid construction, minimal environmental impact, and significant economic benefits [1][2][3][4]. However, the unpredictability of high-temperature scenarios in real-world applications, such as fires and high-temperature industrial processes, places emphasis on the safety and temperature distribution of these culverts [5][6][7]. Specifically, the joints, a crucial part of the culverts, play a pivotal role in determining the overall safety of the structure under high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant focus of extant research methodologies has been placed upon the analysis of prefabricated box culverts under ambient temperature conditions, leaving the phenomena under elevated temperature states somewhat underexplored. Additionally, it has been observed that prior investigations into thermal stress within prefabricated box culverts have typically been constrained to singular loading conditions [14][15][16], thereby overlooking the intricate loading scenarios that may manifest in practical engineering endeavors, such as cyclic loading. Consequently, this has culminated in a partial comprehension of the seismic resilience of prefabricated box culverts when subjected to extreme conditions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%